PERANCANGAN KAPAL TUNDA 2 X 850 HP SEBAGAISARANA PENUNJANG KELUAR MASUK KAPAL BESAR DIDAERAH PELABUHAN TANJUNG PERAK SURABAYA - Rivaldy Amiyono Saputro, (2020)
Indonesia which is an archipelago make us not forget about its history and culture.Especially sea transportation that is more affordable than land or air transportation. Using sea transportation can facilitate human to move around and send lots amount of package. To transport package and passenger a ship is needed. Among freighter there is a boat that is as important to sea transportation, it is tug boat. With tug boat, another boat can lean back or leave the port for cruise safety with the help of tug boat. At least fifty units of boat coming in and out Tanjung Perak port daily through cruise line in west Surabaya. It means there is at least 1.500 units of boat passing by cruise line in west Surabaya monthly. How risky it is if Tanjung Perak port doesn't have supporting facilities like tug boat. Also there is shipwreck because it's too old and collision between boats or reef. With that being said writer make a design of tug boat to increase the amount of tug boat because of shipwreck to help other boat lean back or leave the port. So writer can help Tanjung Perak harbour to support sea transportation in Surabaya port area.